A study on finite element of pre damaged stress concentration factor for a composite laminate member with central circular - Ahmed, T.; Choudhry, R. S.; Shah, Atta Ur Rehman; Saeed, Hasan Aftab (Journal of mechanical science and technology, 2018)
The study investigates the pre damaged stress concentration factor (SCF) for a composite laminate member (CLM) with central circular hole subjected to tensile loading. The presence of holes yields high stress concentrations in the structural members termed as stress raiser and often regarded as an important design deriver. The pre damaged SCF refers to the stress concentrations within elastic (undamaged) range of the CLM prior to the failure initiation. The traditional experimental and analytical methods for the estimation of SCF offer macro level behaviour which is not considered appropriate for CLM where lamina by lamina behaviour is more significant. A meso level finite element (FE) model is presented to capture the lamina by lamina influence on the overall SCF for a CLM using commercial software Abaqus. The paper deals with the fundamental influencing factors such as laminae orientation effect, stress distribution effect around periphery of the hole, decaying effect and ligament effect on SCF for CLM. Analytical models have been formulated to validate the FE models. The results of FE models have been found in close agreement with the analytical results.